DURASI DAN FREKUENSI SAKIT BALITA DENGAN TERJADINYA STUNTING PADA ANAK SD DI KECAMATAN MALALAYANG KOTA MANADO - Naomi Marie Tando (POLTEKKES KEMENKES MANADO, 2012)
Chronic malnutrition can cause stunted body growth (stunting) and state intelligencealso affects the learning achievement of children Children who suffer from malnutrition(stunting) has a weight average IQ 11 points lower than the average of children who arenot stunted. This research is an observational study with a case-control study design.Subjects in this study were elementary school students grades 1 District Malalayangtotaling 78 people, divided into 2 groups: the case group and control group, each groupconsisting of 39 people. Based on a statistical test to the basic characteristics of thestudy subjects in general, there is no difference in subject age, height, weight, duration,frequency of pain, and the treatment (p<0.05), and height for age was no difference(p>0.05). There is a significant correlation between the frequency of illness >6 times ayear by the occurrence of stunting (p<0.05) in other words the subject of pain frequency>6 times a year are at risk are more likely to be stunted compared to the frequency ofpain ≤6 times a year, but there was no correlation between duration of illness >3 dayswith the occurrence of stunting (p>0.05), but the duration of illness in subjects >3 dayshad a risk two times more likely to be stunted than those who had a duration of illness≤3 days.